2011
DOI: 10.1111/j.1937-5956.2010.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Relationship Among Capacity, Pricing, and Inventory in a Make‐to‐Stock System

Abstract: W e address the simultaneous determination of pricing, production, and capacity investment decisions by a monopolistic firm in a multi-period setting under demand uncertainty. We analyze the optimal decision with particular emphasis on the relationship between price and capacity. We consider models that allow for either bi-directional price changes or models with markdowns only, and in the latter case we prove that capacity and price are strategic substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Prior literature often models the capacity adjustment cost by Gðj À j 0 Þ ¼ Àg 1 ðj À j 0 Þ À þ g 2 ðj À j 0 Þ þ , where g 1 (g 2 ) is the return (cost) from using one less (more) unit of capacity (cf. Angelus andPorteus 2002 andAllon andZeevi 2011). We adopt this structure, as it provides a tractable and practical way to model the cost.…”
Section: Evolving Toward Decision Scenariosmentioning
confidence: 99%
“…Prior literature often models the capacity adjustment cost by Gðj À j 0 Þ ¼ Àg 1 ðj À j 0 Þ À þ g 2 ðj À j 0 Þ þ , where g 1 (g 2 ) is the return (cost) from using one less (more) unit of capacity (cf. Angelus andPorteus 2002 andAllon andZeevi 2011). We adopt this structure, as it provides a tractable and practical way to model the cost.…”
Section: Evolving Toward Decision Scenariosmentioning
confidence: 99%
“…The simultaneous determination of pricing, resource utilization, and capacity management decisions under demand uncertainty has been broadly studied in recent years (e.g., Allon and Zeevi 2011, Chayet et al 2011, Gans and Savin 2007, Kostami et al 2017, Lee and Ward 2019, Qi et al 2019. Most of this literature uses queuing theory to model customers' behavior, except for a few papers (e.g., Kostami et al 2017, Qi et al 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of this literature uses queuing theory to model customers' behavior, except for a few papers (e.g., Kostami et al 2017, Qi et al 2019. Allon and Zeevi (2011) model the simultaneous determination of pricing, production and capacity investment decisions by a monopolistic firm in a multi-period setting under demand uncertainty. A service provider is modeled as a queue with a given service rate and the question is how to determine the optimal price and priority rule assuming that customers are sensitive to both estimated cost and waiting time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…m (S, +∞) be the subspace of L 2 m (R) of functions which vanish on (−∞, S). Similarly let W 1,2 m (S, +∞) be the subspace of W 1,2 m (R) of functions which vanish on (−∞, S).…”
Section: Verification Theoremmentioning
confidence: 99%
“…In literature, it is shown that the BSLP policy is the underlying structure of the optimal strategy, even when perturbations of the general setup have been made to fit various business scenarios, see for example [1], [14] [16], [20], [24] and [25].…”
mentioning
confidence: 99%